"Barcelona or die": Understanding illegal migration from Senegal - Linguère Mbaye (IZA Journal of Migration, 2014)
Fatalities from illegal immigration from Africa to Europe are a grave reality. The phenomenon represents a major challenge for both home and host countries. Nonetheless, almost nothing is known about how the motivations of potentially illegally migrating individuals are formed. This paper aims to explain the factors behind the formation of the willingness to migrate illegally knowing that death might occur during the trip. I focus on the role of expectations, friends and relatives who have migrated and host countries policies. By using an original survey among Senegalese residing in Dakar in 2006-2007, I show that potential illegal migrants are willing to accept a substantial risk of death. I find that high expectations and migrant networks are positively related with illegal migration motivations. Surprisingly, I find that stricter immigration policies deter potential legal migrants much more than potential illegal migrants.
Keywords: F22; O15; 330; Illegal migration; Risk attitude; Sub-Saharan Africa; Senegal